Kepuasan Followers Akun X @KDRAMA_MENFESS terhadap Film "My Annoying Brother" Versi Korea Selatan dan Indonesia - Karisga, Aminatuzzuhria; Mustika, Sri; Corliana, Tellys (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Indonesian people's high interest in South Korea Selatann films and dramas has encouraged local production houses to remake South Korea Selatann box office films, one of which is My Annoying Brother. This study aims to analyze and compare the level of audience satisfaction with the South Korea Selatann version and the Indonesian version based on the Uses and Gratifications theory. The method used is a quantitative approach with a survey of 385 respondents who are followers of the @kdrama_menfess account, which was selected using a purposive sampling technique based on the Lemeshow formula (with a margin of error of 5% and a confidence level of 95%). Data was collected through a Likert scale questionnaire and analyzed using SPSS with the Wilcoxon Signed Rank test. The results showed that the majority of respondents (83.9%) were more satisfied with the South Korea Selatann version, especially on the emotional aspect, with the highest score on the affective indicator (GO = 13.48). This finding was supported by the significant difference (Z = -14.984; p < 0.001) between the two versions. Comparative analysis also revealed that 21-25 year olds respondents showed a stronger preference for the Korea Selatann version than other groups. The Indonesian version was appreciated for its local cultural adaptation efforts, but lacked in presenting deep emotional intensity, especially in the key scene of the brother-sister relationship. This study suggests more contextualized cultural adaptation strategies, such as the selection of actors who fit the emotional character and the reinforcement of local narratives.The implication is that production houses can consider affective factors and character identification when adapting foreign films to meet the emotional expectations of local audiences.